Library Research Skills: A Needs Assessment for Graduate Student Workshops. - Kristin Hoffmann; Vivian Feng; Fred Antwi-Nsiah; Meagan Stanley (Issues in Science and Technology Librarianship, 2008)
Information literacy instruction programs for graduate students can be challenging to develop. One solution is to develop non-course-based, non-mandatory library instruction programs, in order to meet the information literacy needs of as many graduate students as possible. This was the approach taken by the Taylor Library at the University of Western Ontario, as we embarked on the development of a program for students in the areas of engineering, health sciences, medicine & dentistry, and science. As a first step, we conducted a needs assessment study via focus groups and an online survey. The study looked at graduate student perceptions of their library research needs, their preferences for learning about library research, and the appropriateness of a common instruction program for students in these disciplines. We found that graduate students wanted to learn about strategies for finding information, bibliographic management tools such as RefWorks, and tools for keeping current with scholarly literature. Students preferred online instruction, although in-person workshops were also found to be valuable. Students in all four faculties identified common information literacy needs, while expressing a desire for subject-specific instruction. [ABSTRACT FROM AUTHOR]